Knee crepitus is prevalent in women with patellofemoral pain, but is not related with function, physical activity and pain - de Oliveira Silva, Danilo [UNESP] (2018)
Objectives: (i) To assess the reliability of knee crepitus measures, (ii) to investigate the association between knee crepitus and PFP; (iii) to investigate the relationship between knee crepitus with self-reported function, physical activity and pain. Design: Cross-sectional. Setting: Laboratory-based study. Participants: 165 women with PFP and 158 pain-free women. Main outcome measures: Knee crepitus test, anterior knee pain scale (AKPS) and self-reported worst knee pain in the last month, knee pain after 10 squats and knee pain after 10 stairs climbing. Results: Knee crepitus clinical test presented high reliability Kappa value for PFP group was 0.860 and for pain-free group was 0.906. There is a significantly greater proportion of those with crepitus in the PFP group than in the pain-free group (OR = 4.19). Knee crepitus had no relationship with function (rpb = 0.03; p = 0.727), physical activity level (rpb = 0.010; p = 0.193), worst pain (rpb = 0.11; p = 0.141), pain climbing stairs (rpb = 0.10; p = 0.194) and pain squatting (rpb = 0.02; p = 0.802). Conclusion: Women who presents knee crepitus have 4 times greater odds to be in a group with PFP compared to those who do not. However, knee crepitus has no relationship with self-reported clinical outcomes of women with PFP.